2021
DOI: 10.1177/23742895211002816
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Alignment of Pathology Residency With Practice II: Findings and Implications

Abstract: This article presents findings from a 4-year series of surveys of new-in-practice pathologists, and a survey of physician employers of new pathologists, assessing how pathology graduate medical education prepares its graduates for practice. Using the methodology described in our previous study, we develop evidence for the importance of residency training for various practice areas, comparing findings over different practice settings, sizes, and lengths of time in practice. The principal findings are (1) while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Additionally, recent reports on qualities that pathology employers seek and those in which pathology trainees believe they are deficient include areas of billing/coding, laboratory management, and molecular pathology, all of which are aspects of graduated responsibility in pathology training. 14 , 15 While not directly assessed in our survey, in the 6-day cycle, residents are taught the aspects of billing and are expected to address and correct coding issues with cases. Additionally, residents are the point person for all laboratory issues, and residents triage for molecular studies, including fluorescent in-situ hybridization (FISH), next-generation sequencing, and methylation profiling.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent reports on qualities that pathology employers seek and those in which pathology trainees believe they are deficient include areas of billing/coding, laboratory management, and molecular pathology, all of which are aspects of graduated responsibility in pathology training. 14 , 15 While not directly assessed in our survey, in the 6-day cycle, residents are taught the aspects of billing and are expected to address and correct coding issues with cases. Additionally, residents are the point person for all laboratory issues, and residents triage for molecular studies, including fluorescent in-situ hybridization (FISH), next-generation sequencing, and methylation profiling.…”
Section: Discussionmentioning
confidence: 99%
“…EC using D-RECT has been assessed in various local and international studies [ 19 ]. However, these studies involved different disciplines [ 3 , 19 21 ], and the nature of EC depends upon the nature of the setting, i.e., each unique specialty and sub-specialty [ 1 , 18 , 22 , 23 ]. The current study, therefore, assessed the EC of a PG pathology residency program by administering D-RECT and was conducted considering the need for future research in more focused areas by examining the individual disciplines to increase the likelihood of ruling out subject-specific differences [ 24 ], mainly when the same climate index can be used even with different stakeholders [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2017-2018, 97% of new-in-practice pathologists reported that they had completed one or more subspecialty fellowships, and 29% reported completing two or more subspecialty fellowships. 4 A contemporary investigation of the demand for BB/TM-trained pathologists in the workforce is needed and might assure fellowship applicants that there is a robust BB/TM job market awaiting them. Additional strategies to improve recruitment into BB/TM fellowships could include proactively encouraging applications from disciplines beyond pathology and emphasizing BB/TM's integral role in stem cell transplantation and cellular therapy.…”
mentioning
confidence: 99%